Desalinated water production optimisation using a high temperature reactor in a cogeneration mode. (1st January 2003) - Lecomte, Michel; Bandelier, Philippe
Production of desalinated water requires energy whether it is heat in evaporating processes or electricity for pumping at high pressure in reserve osmosis processes. In any of these processes, energy represents a substantial share of the final soft water cost, in the range of 50% for the MED process, the remaining part being the amortisation of the desalination unit and its maintenance and operation costs. Whilst efforts to improve the efficiency of the desalination unit and to decrease its operating and maintenance costs help decrease the water cost, a major effort in lowering water cost should come from the energy part. This is where the specificity of nuclear power and in particular of high temperature gas cooled reactors (HTRs) appears interesting. Nuclear plants are characterised by a high capital cost and low fuel cost; therefore, it is advantageous to base load them. Nevertheless, since electricity cannot be stored on a large scale, the plants must load follow, which means that during low consumption hours, electricity is potentially available at the marginal fuel cost which is very low. We will consider these facts in detail in the following, particularly specific HTR characteristics which permit lowering energy costs.